Bone regeneration in rat using polycaprolactone/gelatin/epinephrine scaffold. (2nd December 2021) - Ehterami, Arian; Khastar, Hossein; Soleimannejad, Mostafa; Salehi, Majid; Nazarnezhad, Simin; Majidi Ghatar, Jila; Bit, Arindam; Jafarisani, Moslem; Abbaszadeh-Goudarzi, Ghasem; Shariatifar, Nabi
Abstract: Solid supports like the extracellular matrix network are necessary for bone cell attachment and start healing in the damaged bone. Scaffolds which are made of different materials are widely used as a supportive structure in bone tissue engineering. In the current study, a 3D polycaprolactone/gelatin bone scaffold was developed by blending electrospinning and freeze-drying techniques for bone tissue engineering. To improve the efficiency of the scaffold, different concentrations of epinephrine (EP) due to its effect on bone healing were loaded. Fabricated scaffolds were characterized by different tests such as surface morphology, FTIR, porosity, compressive strength, water contact angle, and degradation rate. The interaction between prepared scaffolds and blood and cells was evaluated by hemolysis, and MTT test, respectively, and bone healing was evaluated by a rat calvaria defect model. Based on the results, the porosity of scaffolds was about 75% and by adding EP, mechanical strength decreased while due to the hydrophilic properties of it, degradation rate increased. In vivo and in vitro studies showed the best cell proliferation and bone healing were in PCL/gelatin/EP1% treated group. These results showed the positive effect of fabricated scaffold on osteogenesis and bone healing and the possibility of using it in clinical trials.